A peep into an African kitchen : perspectives of Onitsha, Nigeria - Egbuna, Ngozi (Enugu, Nigeria : Delta Publications (Nigeria) Limited, 2005)
This book records and highlights some basic values and cultural significance of the African cuisine from the perspectives of native food customs of Onitsha people of South - Eastern Nigeria.
Includes bibliographical references and index
Includes bibliographical references and index.
hza 30/01/2019
Loans
Keywords: Cooking, Nigerian; Cooking; Onitsha (Nigeria)